2015
DOI: 10.1186/s12866-015-0528-z
|View full text |Cite
|
Sign up to set email alerts
|

Xpert MTB/RIF assay can be used on archived gastric aspirate and induced sputum samples for sensitive diagnosis of paediatric tuberculosis

Abstract: BackgroundTuberculosis (TB) in children is neglected, mainly due to lack of sensitive diagnostic tools. Recently Xpert MTB/RIF assay has revolutionized the diagnostic field, but its usefulness in pediatric TB has not been reported from India and no report is available on its use on long term archived samples.MethodsWe recruited 130 pediatric patients with probable intrathoracic tuberculosis and their gastric aspirate (GA) and induced sputum (IS) samples on 2 consecutive days were collected between January 2009… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 27 publications
3
32
1
1
Order By: Relevance
“…In addition, we found high sensitivity and specificity for MTBc and RIF resistance detection that compared well to the previous versions of the assay [4]. Most published reports of Xpert assay performance were conducted using the previous versions of the assay; our findings represent one of the first large studies reporting G4 Xpert assay performance and add to the growing literature [1922] in both high- and low-TB prevalence settings.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, we found high sensitivity and specificity for MTBc and RIF resistance detection that compared well to the previous versions of the assay [4]. Most published reports of Xpert assay performance were conducted using the previous versions of the assay; our findings represent one of the first large studies reporting G4 Xpert assay performance and add to the growing literature [1922] in both high- and low-TB prevalence settings.…”
Section: Discussionsupporting
confidence: 73%
“…28 We reported an Xpert sensitivity of 83% using positive Xpert and/or culture as a reference standard, compared to a pooled sensitivity in GS of 78% using culture as the gold standard reported in a systematic review by Maynard et al, 29 and a sensitivity of 90.4% for all types of pulmonary specimens reported by Chang et al 30 The majority of the patients tested (78%) had a risk of DR-TB, and Xpert testing made rapid DST results available for RMP in 257/313 TB cases.…”
Section: Discussionmentioning
confidence: 99%
“…For establishing a definitive diagnosis of childhood PTB, multiple or repeated decision-making tests (such as MTB culture, nucleic acid test or sequencing) on RTS are often required. The added diagnostic yield from combined tests seems much higher than repeated test [15][16], although this was not extensively assessed in our study. A study from South Africa suggested that the incremental increase in sensitivity from testing a second specimen was 27.8% for MTB/RIF in smear-negative cases [17].…”
Section: Discussionmentioning
confidence: 72%